Efektivitas Penggunaan Aplikasi Kasda Online Dalam Pelayanan Non Tunai Pada PT Bank Sulutgo Wilayah Provinsi Gorontalo - Stevani Priatno, Ilvana; Gobel, Lisda Van; Nggilu , Rukiah (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2025)
This study aims to analyze the effectiveness of the Kasda Online application in supporting non-cash services for regional financial management within the operational area of PT Bank SulutGo in Gorontalo Province. The research is grounded in national policies on the electronification of regional government transactions, which demand efficiency, transparency, and accountability in public financial governance. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation, and analyzed with the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing with triangulation. The results show that the application has a positive impact on accelerating transaction processes, improving time and cost efficiency, and enhancing budget disbursement transparency. However, several obstacles were identified, including technical disruptions, limited internet access, and low digital literacy in certain regencies. Users’ perceptions of the application are generally positive, though there remains a need for technical training and improvements to the system’s interface. The study concludes that Approximately 70–80% of users perceive Kasda Online as effective in supporting non-cash services, while around 20–30% still experience barriers related to infrastructure and technical skills.